Sodelovanje delodajalcev in delavskih predstavnikov pri načrtovanju in izvajanju izobraževanja v podjetjih - Franca, Valentina (Delavci in delodajalci, 2014)
The article focuses on whether and how collective and other agreements made between employee representatives and employers can be used to upgrade the legal regulation concerning employee education, both as regards employee referral as well as training on own initiative. The analysis shows unexploited possibilities of such arrangements, particularly in (strategic) education planning and joint approaches to the provision of funds for these purposes.
Keywords: izobraževanje; kolektivne delovne pogodbe; pogodba o zaposlitvi; sindikati; zaposleni